SYNTHESIS AND PERFORMANCE OF NANO BIOCHAR BASED ADSORBENT FROM FOREST RESIDUE LIGNOCELLULOSE COATED ON LUFFA AEGYPTIACA SPONGE FOR ADSORPTION OF HEAVY METAL HEXAVALENT CHROMIUM - Yulia, Elfi
Adsorbents have an essential role in the adsorption process, which involves the sorption of contaminants from the liquid phase onto the surface of a solid. This process is effectively used as a solution to reduce heavy metals such as hexavalent chromium (Cr(VI)), through the utilization of active functional groups and surface area of the adsorbent. This study developed the adsorbent using a green technology approach, utilizing lignocellulose-based biochar from forest residues. The biochar was processed into nanoparticles through a milling technique with an optimal duration of 4 hours, producing biochar with an average size of 282.7 nm. To increase the adsorption efficiency, the nano biochar was combined with natural polymers chitosan and alginate, then attached to the Luffa aegyptiaca sponge, resulting in a La-NBCA composite adsorbent. Physically, applying the adsorbent layer on the luffa sponge resulted in a more rigid structure, with an even distribution of adsorbent across the surface, facilitating its application in liquid systems. The raw materials and La-NBCA adsorbent were characterized to study the functional groups, morphology, surface area, and adsorption ability of the adsorbent. The functional group characterization results showed the presence of hydrogen bonds (O-H), C-H bonds, C-C bonds, carboxyl functional groups (C=O), C=C bonds, N-H bonds, and carbonate ions, all of which play a role in the heavy metal adsorption process. Morphological analysis of the adsorbent layer showed an even distribution of particles covering the surface of the luffa sponge with a surface roughness profile of 851.3 ?m x 1227 ?m x 255 ?m. After heavy metal adsorption, heavy metal particles adhered to the luffa surface indicating that heavy ions were successfully adsorbed by the adsorbent. Batch adsorption tests also showed that the La-NBCA adsorbent layer was highly effective in removing heavy metal Cr (VI) from the solution, demonstrating its potential for practical applications. The performance of La-NBCA adsorbent in adsorbing Cr(VI) shows that increasing the mass or number of adsorbent layers and decreasing the initial iv concentration of Cr(VI) can increase the adsorption efficiency, with the highest efficiency of 88% on three layers of La-NBCA at 12 mg/L Cr(VI). The adsorption capacity at equilibrium conditions (qe) can be calculated using the curve fittingnonlinear regression method with the Pseudo-First-Order model equation, resulting in R2 values > 0.99 for all test samples. The more significant number of adsorbents used at the same contact time causes the adsorption capacity of the adsorbent (mg/g) used to be smaller, where 3 layers of La-NBCA in 12 mg/L Cr(VI) has a capacity of 1.03 mg/g while one layer of La-NBCA in 25 mg/L Cr(VI). Furthermore, the adsorption mechanism of La-NBCA adsorbent was analyzed by modeling the adsorption kinetics of the Pseudo First Order Model (PFO), Pseudo Second Order Model (PSO), Intraparticle Diffusion (IP), and Simple Elovich and showed that all four models were fitting to explain the adsorption mechanism. In addition, the Langmuir adsorption isotherm model showed the best fit and indicated that the adsorbent surface was homogeneous and adsorption occurred in the form of a monolayer. The performance of La-NBCA adsorbent was evaluated in a circulating adsorption column with flow rates between 13 and 38 ml/min. Modeling using a surface model with the adsorption kinetics equation approach and flow rate was performed to describe the relationship between adsorption capacity, contact time, and circulating flow rate. The modeling results showed a high R² value (0.99) with low SSE and RMSE values, indicating a good fit. The modeling results showed the circulation flow rate had a significant effect on the adsorption process, where the optimal rate of 26 ml/min resulted in an adsorption capacity of 6.94 mg/g and the highest efficiency of 63% in 240 min and lower at other flow rates. Keywords: adsorption process, adsorbent, nano biochar, lignocellulosic biochar, forest residue biochar, heavy metal Cr (VI), Luffa aegyptiaca sponge